Influence of roller compaction parameters on properties of granules and quality characteristics of finished product - Olga Oleksandrivna Yuryeva; Yuriy Victorovich Naida; Oksana Volodimirivna Tryhubchak; Svitlana Nicolaivna Gureyeva; Yuliya Anatoliivna Kondratova; Andrew Mihaylovych Goy (Journal of Global Pharma Technology, 2017)
Roller compaction widely used in pharmaceutical industry as alternative to wet granulation. This technology acknowledged as more cost-effective and productive, improves granules properties, which in turn will enhance tableting process.Objective. Powder mixtures for products with immediate release: Glucose monohydrate 75 g granulated powder, Sodium picosulfate 7.5 mg tablets and Amlodipine/Valsartan 5/160 mg coated tablets.Methods. In this research the analysis of influence roller compaction parameters on flowability, bulk density and particle size distribution of granules was performed. Tablets, compressed from these granules tested for analytical properties (assay, dissolution, impurities) and technological properties (disintegration, friability, hardness).Results. For Glucose monohydrate 75 g optimum compaction parameters are primed: hydraulic pressure 50 bar and 1,25 mm screen size, with roller speed 11,5 rpm and roller gap 2,0 mm. The research of Sodium picosulfate 7.5 mg allowed determining the optimum compaction parameters: 50 bar hydraulic pressure, 0,8 mm screen size, 2.5 mm roller gap, roller speed 11 rpm, mill speed 80 rpm. For Amlodipine/Valsartan 5/160 mg optimal values of properties are indicated by regression analyses.Conclusion. As the result, influence of roller compaction parameters on quality characteristics of finished product and perspective of this technology for solid dosage forms manufacturing confirmed.